The Effect of Landscape Composition on The Diversity and Abundance of Ants (Hymenoptera: Formicidae) in Cabbage Cultivation Area - Amalia, Dinda Rayhan; Rizali, Akhmad (Journal of Tropical Plant Protection, 2024)
Cabbage (Brassica oleracea var. capitata) is a vegetable with significant potential for cultivation due to its high economic value. However, cabbage production experiences fluctuations each year primarily due to pest factors. To control these pests, natural enemies such as ants can be utilized. Ants are highly sensitive to changes in their habitat, making them known as environmental bioindicators. Additionally, landscape structure can influence the presence of insects, including predators and parasitoids. This study aims to determine the effects of cultivation methods, habitat conditions, and landscape composition on ant diversity and abundance. The research was conducted from November 2022 to May 2023 across 12 fields in four different sub-districts: Pujon, Tumpang, Poncokusumo, and Purwodadi. The research process included landscape mapping and characterization, determination of observation plots, trap installation and sampling, species identification, collection of supporting data, and data analysis. The study yielded a total of 4,053 individuals representing 26 genera and 52 morphospecies. The ant species with the highest abundance was Lophomyrmex sp.3, while the greatest diversity was observed within the genus Tetramorium. Insecticide application and plant age did not significantly affect ant diversity and abundance; however, elevation did influence ant abundance. Additionally, landscape composition, particularly the class area (CA) of natural habitats, correlated positively with both ant diversity and abundance.